An integrative analysis of genome‐wide methylation and expression in ameloblastoma: A pilot study - Pongpanich, Monnat; Sanguansin, Sirima; Kengkarn, Sudaporn; Chaiwongkot, Arkom; Klongnoi, Boworn; Kitkumthorn, Nakarin (Oral diseases, 2021)
Objective DNA methylation regulates the expression of various genes involved in tumorigenesis. Ameloblastoma is a benign odontogenic jaw tumor. It is locally aggressive with a high level of recurrence. A delay in treatment can lead to severe facial disfigurement. To the best of our knowledge, this is the first integrated analysis of DNA methylation and gene expression in ameloblastoma with the aim to identify genes that may be regulated by DNA methylation. Materials and Methods We used an Infinium MethylationEPIC array to measure genome‐wide methylation and the Illumina HiSeq platform to obtain gene expression data in ameloblastoma tissues from five patients and dental follicles from three healthy subjects. An integration analysis was performed using City of Hope CpG Island Analysis Pipeline software. Results We identified 25,255 differentially methylated CpG sites and 17 differentially methylated CpG islands; six of the islands were negatively correlated with the expression of BAIAP2, DUSP6, FGFR2, FOXF2, NID2, and PAK6. Pyrosequencing and immunostaining techniques were further used to validate FGFR2, NID2, and PAK6. Conclusions This analysis identifies a group of novel genes that may be regulated by DNA methylation and will possibly lead to new insights into the pathology and invasion mechanism of ameloblastoma.